The Impact of Work Motivation, Leadership Style, and Key Performance Indicators (KPI) on Teacher Work Discipline - Didi Rianto; Moh Bukhori; Justita Dura (Journal of Educational Management Research, 2026)
This study aims to analyze the influence of work motivation, the principal’s leadership style, and the implementation of Key Performance Indicators (KPIs) on teacher work discipline. Teacher work discipline is a crucial factor in supporting the effectiveness of the learning process and achieving educational goals. This study employed a quantitative, survey-based approach. The study population comprised 55 teachers, of whom 32 were permanent foundation teachers selected using a purposive sampling technique. Primary data were collected through a Likert-scale questionnaire, while secondary data were obtained from teacher attendance records, administrative submissions, and task completion records. Data analysis was conducted using multiple linear regression. The results showed that work motivation, the principal’s leadership style, and KPIs partially had a positive and significant effect on teacher work discipline. Furthermore, secondary data analysis strengthened the study findings by indicating that teacher attendance, the accuracy of administrative submission, and task completion reflected a level of work discipline that still needed improvement. This study concluded that increasing work motivation, applying an effective leadership style, and implementing clear, measurable KPIs can sustainably improve teacher work discipline. The findings of this study are expected to serve as a basis for schools in formulating more effective human resource management policies.